2013
DOI: 10.1523/jneurosci.4165-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Deletion ofAbca7Increases Cerebral Amyloid-β Accumulation in the J20 Mouse Model of Alzheimer's Disease

Abstract: ATP-binding cassette transporter A7 (ABCA7) is expressed in the brain and has been detected in macrophages, microglia, and neurons. ABCA7 promotes efflux of lipids from cells to apolipoproteins and can also regulate phagocytosis and modulate processing of amyloid precursor protein (APP) to generate the Alzheimer's disease (AD) amyloid-␤ (A␤) peptide. Genome-wide association studies have indicated that ABCA7 single nucleotide polymorphisms confer increased risk for late-onset AD; however, the role that ABCA7 pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
160
3
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(174 citation statements)
references
References 44 publications
8
160
3
3
Order By: Relevance
“…In addition, phagocytic clearance of oligomeric Aβ was found to be impaired in ABCA7-deficient macrophages compared with wild-type (WT) macrophages [14]. In general agreement with these cell culture studies, work in AD mouse models has also provided evidence supporting a role for ABCA7 in amyloid homoeostasis.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…In addition, phagocytic clearance of oligomeric Aβ was found to be impaired in ABCA7-deficient macrophages compared with wild-type (WT) macrophages [14]. In general agreement with these cell culture studies, work in AD mouse models has also provided evidence supporting a role for ABCA7 in amyloid homoeostasis.…”
Section: Introductionsupporting
confidence: 67%
“…In general agreement with these cell culture studies, work in AD mouse models has also provided evidence supporting a role for ABCA7 in amyloid homoeostasis. In the J20 AD transgenic mouse model, deletion of ABCA7 led to a doubling of insoluble Aβ levels and amyloid plaques in mice assessed at 17 months of age [14]. An independent study using the same Abca7 null (Abca7 − / − ) mouse line but crossed with the TgCRND8 AD mouse model revealed an increase in the area of dense plaques at 18 weeks of age that the authors concluded was likely to be a reflection of the increased production of Aβ in the TgCRND8-Abca7 − / − mice [13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to nonsynonymous ABCA7 variants, we observed a splice site, a stop mutation, and frameshift deletions, suggesting a loss‐of‐function mechanism associated with LOAD. Our recent functional studies of ABCA7 strongly support such a possibility,29, 30 because suppression of ABCA7 in vitro and in vivo resulted in an elevation of amyloid production. The complex function of ABCA7 includes mediation of the biogenesis of high‐density lipoprotein with cellular lipid and helical apolipoproteins,31 as well as function in apolipoprotein‐mediated phospholipid and cholesterol efflux from cells 32.…”
Section: Discussionmentioning
confidence: 76%
“…Kim et al found that ABCA7 knockout mice crossed with J20 amyloidogenic mice had double the amount of insoluble amyloid‐ β concentration and plaque levels in the brain compared to J20 mice 24. The ability to phagocytose amyloid‐ β ‐oligomers in isolated microglia and macrophages was reduced in ABCA7 knockout mice compared to wild‐type mice 12.…”
Section: Discussionmentioning
confidence: 99%
“…ABCA7 is highly expressed in brain tissue,9, 21, 22 most abundant in microglia and oligodendrocytes 7, 23. Previous studies comparing ABCA7 knock‐out mice with wild‐type mice or J20 amyloidogenic mice demonstrate that ABCA7 is involved in clearance of amyloid‐ β in the brain through phagocytosis 12, 24. Furthermore, early studies on ABCA7 explored lipid efflux capacities and suggested that ABCA7 contributes to phospholipid and cholesterol transport 8, 9, 10, 21, 25, 26, 27.…”
Section: Introductionmentioning
confidence: 99%